PERAN DISIPLIN KERJA DAN MOTIVASI DALAM MEMBENTUK KINERJA KARYAWAN - Syamsul Muarif (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2026)
This study aims to examine the role of work discipline and motivation in shaping employee performance at PT. Abadi Makmur using a descriptive quantitative approach through questionnaires distributed to all 90 employees with a saturated sampling technique. Data were analyzed using linear regression to explore the relationships among variables. The findings reveal that work discipline has a significant role in shaping employee performance, particularly in fostering consistent work behavior such as adherence to rules, punctuality, and job responsibility. Meanwhile, motivation does not show a significant effect on employee performance when examined individually, although it still functions as an internal driver that influences work enthusiasm and initiative. However, when considered simultaneously, work discipline and motivation complement each other in creating more effective and sustainable employee performance. These findings highlight that improving employee performance requires not only the enforcement of work discipline but also the proper integration of motivational strategies in human resource management.